RAINFALL PROJECTIONS USING CMIP6 SCENARIOS IN THE CIRARAB WATERSHED - Hidayah, Kuny; Sekaranom, Andung Bayu; Suprayogi, Slamet (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Climate change has been identified in the Cirarab watershed by looking at records of extreme rainfall events. This study aims to develop a scenario of climate change impacts at the watershed scale, especially from the aspect of changes in rainfall patterns in the Cirarab watershed until 2050. This research uses a descriptive quantitative method with a spatial-temporal approach, using secondary data obtained from the official databases of BMKG, CMIP6, and relevant literature. The analysis technique used is statistical downscaling. The results stated that based on climate change scenarios, the annual rainfall pattern in the Cirarab watershed remains stable with a monsoon climate type, marked by a single peak in the rainy season. Spatial variations in monthly rainfall are minimal due to the watershed’s flat topography. However, rainfall variability during the rainy season leads to a temporal shift in the peak, indicating changes in rainfall timing despite overall pattern stability. Keywords: Cirarab Watershed, Climate Change, CMIP6